How grammar links concepts verb-mediated constructions, attribution, perspectivizing - Ungerer, Friedrich (Human cognitive processing ;, 2017)
The proposed framework of 'concept linking' combines insights of construction grammar with those of traditional functional descriptions to explain particularly challenging but often neglected areas of English grammar such as negation, modality, adverbials and non-finite constructions. To reach this goal the idea of a unified network of constructions is replaced by the triad of verb-mediated constructions, attribution and scope-based perspectivizing, each of them understood as a syntactically effective concept-linking mechanism in its own right, but involved in interfaces with the other mechanisms. In addition, 'concept linking' supplies a novel approach to early child language. It casts fresh light on widely accepted descriptions of early two-word utterances and verb islands in usage-based models of language acquisition and encourages a new view of children's 'mistakes'.